2019
DOI: 10.1177/2158244018823428
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Entry Into Drug Abuse Among Youths in Lafia Metropolis: Implications on Security

Abstract: Abuse of drugs by youths and its detrimental effects on security in Lafia Metropolis have recently attracted public attention. Given this background, it is important to understand the factors that influenced youths to take to drugs and the extent to which involvement in drugs has affected security in the Metropolis and thus explore effective ways toward curbing it. A survey method was adopted with samples drawn from 10 political wards in the Metropolis. Questionnaires were administered on 520 respondents with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…6 It is estimated that the average annual retail cost of psychotropic substances in Nigeria is more than fifteen thousand US dollars, while alcoholic beverages aside from spirit generate more than thirty thousand US dollars from sales to a consumer population of about thirty to thirty-five million people. 7 Other Nigerian studies done include Idowu et al 4 showed that substance abuse is fast becoming a public health concern with 39.0% of the respondents shown to have been abusing tramadol, Okafor 8 in Kwara State also observed increasing youth involvement in substance abuse, Ikoh et al 9 in Lafia, Nasarawa State related street fighting, accidents and robbery to substance abuse among youths and Raimi et al 10 in Yenogoa, Bayelsa State, also discovered that four out of ten persons abuse drugs. All these studies underscore the importance and impact the consequences of substance abuse on the youth in Nigeria particularly and the world in general.…”
mentioning
confidence: 96%
“…6 It is estimated that the average annual retail cost of psychotropic substances in Nigeria is more than fifteen thousand US dollars, while alcoholic beverages aside from spirit generate more than thirty thousand US dollars from sales to a consumer population of about thirty to thirty-five million people. 7 Other Nigerian studies done include Idowu et al 4 showed that substance abuse is fast becoming a public health concern with 39.0% of the respondents shown to have been abusing tramadol, Okafor 8 in Kwara State also observed increasing youth involvement in substance abuse, Ikoh et al 9 in Lafia, Nasarawa State related street fighting, accidents and robbery to substance abuse among youths and Raimi et al 10 in Yenogoa, Bayelsa State, also discovered that four out of ten persons abuse drugs. All these studies underscore the importance and impact the consequences of substance abuse on the youth in Nigeria particularly and the world in general.…”
mentioning
confidence: 96%
“…Substance availability in the community is one of the major predictors of substance abuse among teenagers. Availability may be viewed in terms of the ease at which the substance is procured [37] as well as the effect of advertisement [38]. Both licit substances and some illicit substances such as alcohol, tobacco, and cannabis are readily available and affordable in most societies, this makes it easy for individuals both young and old to able to access the substances.…”
Section: Availabilitymentioning
confidence: 99%
“…Lawal & Aliyu [42] noted in their study on the assessment of causes and effects of drugs and substance abuse among youth that the major cause of adolescent substance abuse is peer pressure and their desire to have fun and enjoy themselves. Furthermore, this could be due to the need to attain a certain social status, adventurous venture, or novelty-seeking [37]. Also, those in romantic relationships influence their partners into joining them to take psychoactive substances [43].…”
Section: Peer Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Research has consistently reported that drug and substance abuse behaviors among students in higher learning institutions is commonly linked to already perceived norm practices amongst age mates. [11] identi ed factors such as peers and media in uence, need to release stress, desire to enjoy the drug, accessibility of drugs, desire to experiment, in uence from guardians and siblings, poor parenting, having trouble in school are key factors in uencing drug and substance abuse. Further, having a problem with the police and unemployment have been reported in most studies to be factors contributing to drug and substance abuse among youth aged between 17 to 28 years old with peer and social media in uence being reported as the most in uential factor.…”
Section: Introductionmentioning
confidence: 99%